1978
DOI: 10.1044/jshd.4301.47
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Cooccurrence of Vocal Tract Dysfunctions in the Speech of a Large Sample of Parkinson Patients

Abstract: In this study, the frequency of occurrence of speech and voice symptoms in 200 Parkinson patients was defined by two expert listeners from high-fidelity tape recordings of conversational speech samples and readings of the sentence version of the Fisher-Logemann Test of Articulation Competence. Specific phonemes that were misarticulated were catalogued. Other vocal-tract dysfunctions, including laryngeal disorders, rate disorders, and hypernasality, were also recorded. Cooccurrence of symptoms in each patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
316
1
18

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 578 publications
(365 citation statements)
references
References 0 publications
17
316
1
18
Order By: Relevance
“…Adjustment to the Portuguese and application to patients with Parkinson's disease of protocol within central origin dysarthrias' assessment Angélica Suelen Fracassi (1) , Ana Rita Gatto (2) , Silke Weber (3) , André Augusto Spadotto (4) , Priscila Watson Ribeiro (5) , Arthur Oscar Schelp (6) RESUMO Objetivo: traduzir e adaptar protocolo desenvolvido por pesquisadores alemães, adequando-o às características fonéticas e linguísticas do português falado no Brasil. Caracterizar os componentes de fala mais alterados na população com doença de Parkinson, comparando-os com grupo de sujeitos normais na mesma faixa etária.…”
Section: Adaptação Para a Língua Portuguesa E Aplicação De Protocolo unclassified
“…Adjustment to the Portuguese and application to patients with Parkinson's disease of protocol within central origin dysarthrias' assessment Angélica Suelen Fracassi (1) , Ana Rita Gatto (2) , Silke Weber (3) , André Augusto Spadotto (4) , Priscila Watson Ribeiro (5) , Arthur Oscar Schelp (6) RESUMO Objetivo: traduzir e adaptar protocolo desenvolvido por pesquisadores alemães, adequando-o às características fonéticas e linguísticas do português falado no Brasil. Caracterizar os componentes de fala mais alterados na população com doença de Parkinson, comparando-os com grupo de sujeitos normais na mesma faixa etária.…”
Section: Adaptação Para a Língua Portuguesa E Aplicação De Protocolo unclassified
“…The recent tracing studies in monkey Jurgens, 2003, 2005) have demonstrated dense reciprocal connections between the laryngeal motor cortex and the putamen and thalamus, yet subcortical control systems and their modulation of cortical and the brain stem centers are virtually unexplored. Significant voice and swallowing deficits seen in Parkinson disease suggest that other regions besides the cortex and medulla are critical to normal laryngeal control for speech and swallowing (Logemann et al, 1977;Robbins et al, 1986). Improved knowledge of the basal ganglia control of the laryngeal musculature might allow for exploration of various neurotransmitter systems to improve laryngeal function in cough, swallow, voice, speech and respiration.…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%
“…Speech symptoms are prevalent in Parkinson's disease (PD; Logemann et al, 1978), with voice changes being the earliest and most common (Holmes et al, 2000). These symptoms cause significant decreases in patient quality of life, often well before obvious changes in speech intelligibility (Miller et al, 2006).…”
Section: Introductionmentioning
confidence: 99%